2022
DOI: 10.1371/journal.pone.0273570
|View full text |Cite
|
Sign up to set email alerts
|

Network analysis based on big data in social media of Korean adolescents’ diet behaviors

Abstract: Adolescents are increasingly interested in weight control; hence, proper health education is important for helping them control their weight properly. This study was designed to pick out social media words that express adolescents’ diet behaviors, and identify the associations and types between such words and the behaviors. It used text-mining techniques and semantic network analysis for related big data collected from the Internet on adolescents’ diet behaviors. Text mining was used to extract meaningful info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…The results also revealed that the recommendation system has more highly significant to the intentions of the individuals than their behavior (Naeem et al, 2022); it means that the recommendation system by companies can boost the intentions of the customers more than their behavior (Le & Liaw, 2017;Müller et al, 2019;Zhang et al, 2022). Information search has also affected customer intention and then after this, it increases the behavior for purchases (Oesterreich et al, 2022;Song et al, 2022). This satisfaction comes because of information provided by the companies through BDA (Akter & Wamba, 2016;Liao & Yang, 2021;Lo & Harvey, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The results also revealed that the recommendation system has more highly significant to the intentions of the individuals than their behavior (Naeem et al, 2022); it means that the recommendation system by companies can boost the intentions of the customers more than their behavior (Le & Liaw, 2017;Müller et al, 2019;Zhang et al, 2022). Information search has also affected customer intention and then after this, it increases the behavior for purchases (Oesterreich et al, 2022;Song et al, 2022). This satisfaction comes because of information provided by the companies through BDA (Akter & Wamba, 2016;Liao & Yang, 2021;Lo & Harvey, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The data collection and analysis processes used in this study are shown in Fig. 1 and this is the same method as described in the previous study ( Song et al, 2022 ). First, we collected data on adolescent stress by crawling online news and blog websites.…”
Section: Methodsmentioning
confidence: 99%
“…Yet another study collected data from search engines widely used in Korea to identify social media words that express adolescents’ dietary behaviours and identify the associations and types of such words and behaviours. It used text-mining techniques and SNA for related big data collected from the Internet on adolescents’ dietary behaviours ( Song et al, 2022 ). A study on physical activity and exercise in school-age youth was conducted to provide a solution by analysing a large number of scientific articles through text mining ( Pans et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%